Pemanfaatan Fitur Bukti Karya pada Platform Merdeka Mengajar di Sekolah Penggerak - Susana, Eva; Lilis Suryani (Universitas Lancang Kuning, 2025)
This research is focused on the use of the Bukti Karya feature on the Platform Merdeka Mengajar which aims to provide a comprehensive overview of how this feature is used in the field, the challenges faced, the solutions taken, as well as the benefits and impacts on the quality of learning at Mutiara Pertiwi 2 Kindergarten. This research was carried out at Mutiara Pertiwi 2 Kindergarten, Babelan District, Bekasi Regency, West Java from July to November 2024. This research is also expected to provide recommendations to increase the use of this feature in Sekolah Penggerak more widely. The researcher used a qualitative approach of descriptive analysis. The data analysis activities used by the researcher are Miles and Huberman data analysis which consist of data collection, data reduction, data presentation and conclusions, which can make the data meaningful. Researchers collect data and information through observation, interviews, discussions and documentation. The use of the Bukti Karya feature on the Platform Merdeka Mengajar that has been carried out at Mutiara Pertiwi 2 Kindergarten can be concluded to be going well. The Bukti Karya feature assists teachers and principals in finding aspirations for learning resources, good practices and teaching module and can share learning documentations. Good practices and teaching modules taken from the Bukti Karya feature are adapted and modified first before being used in daily learning, adjusted to the needs and characteristics of children and learning objectives